GENE ACTION AND ORDER EFFECTS FOR HIGH FRUITING EFFICIENCY IN INTER AND INTRA SPECIFIC HYBRIDS OF COTTON - SAIDA NAIK. D; RAMPRASAD. B, PRASHANTH. Y, PRADEEP. T, SUDARSHANAM. A (The Journal of Research, PJTSAU, 2023)
Quadriallel analysis provides information on all types of gene actions viz., additive, dominance and epistatic components besides giving information on order of parents in double cross combinations for obtaining superior transgressive segregants. Present study was made to obtain information on gene actions controlling the number of bolls per plant in 45 inter and intra specific cotton double cross hybrids from four Gossypium hirsutum L. (Adilabad kapas-1, ADB-39, ARBC-64 and CNH 115) and two Gossypium barbadense L. (Suvin and Phule rukhmai) genotypes. The general and specific combining ability effects were significant. Three double crosses (Adilabad kapas-1 × Phule rukhmai) (ADB-39 × Suvin), (Adilabad kapas-1 × Phule rukhmai) (ARBC-64 × CNH 115) and (ADB-39 × Suvin) (ARBC-64 × CNH 115) recorded high four line interaction effects of lines i, j, k and l due to particular arrangements. Dominance variation found to be more than additive variance while, among the epistatic interaction, additive × additive × additive was high fallowed by dominance × dominance and additive × dominance. Hence pure line development would be more successful with selection in the later generations involving parents derived from above double crosses.